2022
DOI: 10.3390/medicina58060786
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy, Biomechanics, and Reconstruction of the Anterolateral Ligament of the Knee Joint

Abstract: Despite remarkable advances in the clinical outcomes after anterior cruciate ligament reconstructions (ACLRs), residual rotational instability of the knee joint remains a major concern. Since the anterolateral ligament (ALL) on the knee joint has been “rediscovered”, the role of anterolateral structures, including ALL and deep iliotibial band, as secondary stabilizers of anterolateral rotatory instability has gained interest. This interest has led to the resurgence of anterolateral procedures combined with ACL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The importance of ensuring knee stability in the structures analysed (MCL, POL, ALL and medial meniscus) in our study has been widely reported and analysed in the literature; in fact, several biomechanical studies have demonstrated that the ALL acts as a secondary stabilizer of anterolateral rotatory instability [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of ensuring knee stability in the structures analysed (MCL, POL, ALL and medial meniscus) in our study has been widely reported and analysed in the literature; in fact, several biomechanical studies have demonstrated that the ALL acts as a secondary stabilizer of anterolateral rotatory instability [18].…”
Section: Discussionmentioning
confidence: 99%
“…RAMP lesions are associated with notable augmentation of anterior translational mobility and external rotational instability of the tibia [19]. During clinical examination, both types of damage cause an augmentation in motion when the subject is doing the pivot-shift test [6,18,19]. In individuals diagnosed with an ACL injury and accompanying ALL tear or RAMP lesion, complete restoration of knee joint stability is frequently not achieved via ACL reconstruction alone [6,22,24].…”
Section: Introductionmentioning
confidence: 99%
“…Several variable surgical techniques have been developed with promising short-term prognoses [ 1 , 23 , 24 ]. However, some systemic reviews revealed variation in the anatomic footprint and heterogeneous biomechanical results, and the objective measurement of the surgical outcome also varied [ 25 , 26 ]. DePhillipo et al found there was more variability in the femoral tunnel location than in the tibial tunnel.…”
Section: Discussionmentioning
confidence: 99%
“…They noted average comparability for the KT1000 and GNRB and poor comparability for the others. Hence, they concluded that the devices were not comparable [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…ACL reconstruction (ACLR) is, therefore, one of the most common procedures performed in orthopaedic surgery [26].…”
Section: Introductionmentioning
confidence: 99%